Coping with Stress and Psychological Well-Being in University Students from the Peruvian Cities of Lima and Huancayo - Matalinares, María Luisa (2016)
The purpose of this study is to establish the relationship between stress coping styles and psychological well-being. We examined a sample of 934 university students from the cities of Lima and Huancayo, aged between 16 and 22 years. Participants completed the COPE Inventory and the Ryff’s Psychological Well-Being Scales (PWB), both adapted to the Peruvian context. Results show a direct and significant relation between problem-focused and emotion-focused coping strategies and psychological well-being, whereas other coping strategies obtained a significant but indirect relationship